Changes in hematological indicators of foals infected by strongyloidiasis - Гугосьян, Ю. А. (Scientific Progress & Innovations, 2016)
We studied the influence of the pathogen strongyloidiasis on morphological and biochemical indicators of blood infested foals. Research has established that strongyloidiasis infestation is accompanied by anemia, leukocytosis (13,46±1,03 g/l, p>0,001) and eosinophilia (9,3±0,32%, p>0,001). In the blood serum of sick horses evident dysproteinemia with hypoalbuminemia (p>0,001) and hyperglobulinemia (p>0,01), an increase in the activity of alanine and aspartate aminotransferase (p>0,001), the content of total bilirubin (15,12±2,38 mcmol/l, p>0,01), and reduced glucose (3,12±0,92 mmol/l, p>0,05).